In Exercises 23-28, write a rule for \( g \) and then graph each function. Describe the graph of \( g \) as a transformation of th graph of \( f \). (See Example 4.) \( \begin{array}{ll}\text { 23. } f(x)=x^{4}+1, g(x)=f(x+2) & \text { 24. } f(x)=2 x^{3}-2 x^{2}+6, g(x)=-\frac{1}{2} f(x) \\ \text { 25. } f(x)=x^{6}-3 x^{3}+2, g(x)=f(x-1)-3 & \text { 26. } f(x)=x^{5}-2 x+3, g(x)=3 f(x)+1 \\ \text { rule: }(x-1)^{6}-3(x-1)^{3}+2-3 & \text { 28. } f(x)=\frac{1}{2} x^{5}+x^{3}-4 x-4, g(x)=-f(2 x)+1 \\ \text { 27. } f(x)=x^{4}+x^{3}-1, g(x)=f(-x)-5 & \end{array} \)
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Extra Insights
Transformations of functions can be as creative as an artist with a canvas! For example, in exercise 23, the rule for \( g(x) = f(x+2) \) translates the graph of \( f(x) = x^4 + 1 \) two units to the left. The resulting graph will have a similar shape but will peak at a different point. In exercise 24, the function \( g(x) = -\frac{1}{2} f(x) \) flips the graph of \( f(x) = 2x^3 - 2x^2 + 6 \) upside down and compresses it vertically by a factor of 2! It's a wild ride through algebra, giving a totally new vibe to how the function looks!